1995
DOI: 10.1128/jb.177.19.5622-5627.1995
|View full text |Cite
|
Sign up to set email alerts
|

Catabolite inactivation of the yeast maltose transporter occurs in the vacuole after internalization by endocytosis

Abstract: The maltose transporter of Saccharomyces cerevisiae is rapidly degraded during fermentation in the absence of a nitrogen source. The location and mechanism of degradation of the transporter have been investigated. Using mutants defective in endocytosis, we have shown that degradation of this transporter requires internalization by endocytosis. In addition, studies of mutants defective in proteasome or vacuolar proteolysis revealed that degradation occurs in the vacuole and is independent of proteasome function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 49 publications
9
86
0
5
Order By: Relevance
“…Carbon catabolite inactivation affects enzymes of peripheral functions, for example maltose permease and galactose permease (Gorts, 1969 ;De Juan & Lagunas, 1986), as well as enzymes of central functions such as the gluconeogenic enzymes fructose-l,6-bisphosphatase and phosphoenolpyruvate carboxykinase (Holzer, 1976). Vacuolar and proteasomal proteolysis have recently been identified as possible mechanisms of degradation, the former particularly for carrier proteins (Schork et al, 1994;Riballo et al, 1995;Horak & Wolf, 1997).…”
Section: Glucose Control In 5 Cerevisiaementioning
confidence: 99%
“…Carbon catabolite inactivation affects enzymes of peripheral functions, for example maltose permease and galactose permease (Gorts, 1969 ;De Juan & Lagunas, 1986), as well as enzymes of central functions such as the gluconeogenic enzymes fructose-l,6-bisphosphatase and phosphoenolpyruvate carboxykinase (Holzer, 1976). Vacuolar and proteasomal proteolysis have recently been identified as possible mechanisms of degradation, the former particularly for carrier proteins (Schork et al, 1994;Riballo et al, 1995;Horak & Wolf, 1997).…”
Section: Glucose Control In 5 Cerevisiaementioning
confidence: 99%
“…Similarly, another vacuole resident protein, carboxypeptidase Y, is transported to the vacuole by the vacuole protein sorting (Vps) 2 pathway (3-7). Extracellular and plasma membrane proteins can be internalized and delivered to the vacuole by endocytosis (11,12). Moreover, organelles such as peroxisomes can also be targeted to the vacuole for degradation by pexophagy (13,14).…”
mentioning
confidence: 99%
“…To verify the effect of Gly-46 and His-50, a glucose-induced degradation test was conducted for these mutant proteins (Fig. 5B) MAL61p Is Ubiquitinated to a Higher Degree than MAL21p in the Presence of Glucose-It is known that maltose transporters are not internalized until they are ubiquitinated (14). To examine differences in the efficiency of ubiquitination of Mal61p and Mal21p molecules in the presence of glucose, MAL61 and MAL21 were expressed in end4 and npi1 mutant cells, which are deficient in an early stage endocytosis process (37) and ubiquitin-conjugating activity (32,38), respectively.…”
Section: Determination Of the Residues In Mal21pmentioning
confidence: 99%
“…The addition of glucose to maltose-grown yeast cells results in a rapid inactivation of maltose transporters followed by their degradation. This degradation process requires endocytosis of the targeted proteins, their trafficking to the vacuole, and subsequent vacuolar proteolysis (13,14). It has been reported that for various membrane transporters, phosphorylation of Ser, Thr, or Tyr residues and subsequent ubiquitination of the Lys residue are a prerequisite for their internalization on degradation.…”
mentioning
confidence: 99%